PENGEMBANGAN MEDIA MAGIC BOOK “AKTIVITAS ANAK MUSLIM” DALAM MENINGKATKAN NILAI PENDIDIKAN ISLAM ANAK USIA 5-6 TAHUN - Yearin, Tarisa Ananda; Nyayu Soraya; Elsa Cindrya; Saipul Annur; Kurnia Dewi (Early Childhood: Jurnal Pendidikan, 2025)
This research is motivated by the lack of media related to Islamic educational values that are more enjoyable, with innovative and educational learning methods for children. This study aims to develop valid, practical and effective Islamic-based magic book learning media in improving the Islamic educational values of children aged 5-6 years at RA Plus Fatahul Wardah Palembang. The research method used is R&D with a 4D development model. The subjects of the study were 11 children aged 5-6 years at RA Plus Fatahul Wardah Palembang. Data were collected through observation, questionnaires, interviews and documentation and then analyzed using validity, practicality and effectiveness tests to test the quality of the magic book media. The questionnaire sheet and student interview sheet were used to determine student responses to the magic book media. The results showed that the magic book learning media obtained a material validation score of 94.2%, language 76% and media 96.3% which were categorized as very valid. The practicality test of 93.84% was stated as very practical, a small-scale trial of 95% and a large-scale trial of 97.6% which was stated as very effective. Meanwhile, the effectiveness of the magic book media was tested again through a hypothesis test using the t-test, the t-count value was obtained to be greater in absolute terms than the t-table value (| t-count | = 48.50 > t-table = 2.086).